2023
DOI: 10.1136/bmjpo-2022-001752
|View full text |Cite
|
Sign up to set email alerts
|

Early hearing detection and intervention (EHDI) programmes for infants and young children in low-income and middle-income countries in Asia: a systematic review

Abstract: BackgroundEarly hearing detection and intervention (EHDI) measures initiated in high-income countries (HICs) were attempted in low-income and middle-income countries (L&MICs). However, information regarding the models of EHDI, context-specific adaptations made to strategies and outcomes are not known.AimsThe aims of this systematic review were to identify the various models of EHDI used in Asian L&MICs in the published scientific literature and to describe their efficacy and validity.MethodsThe studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
(287 reference statements)
1
6
0
Order By: Relevance
“…17 More relevant to the Philippines, a systematic review of EHDI programs in low-and middle-income countries in Asia revealed three of 82 studies describing "the use of ICT for storing and forwarding results, database management, and sending reminders for follow-up screening". 18 This HeLe evaluation centered on the NHS program and technical / technology inputs, based on the CDC guidelines for evaluating public health surveillance systems. We evaluated information quality (relevance, accuracy, completeness, timeliness) and system quality (availability, usability/ accessibility, functionality, comprehensive data capture, error reduction, and security).…”
Section: Discussionmentioning
confidence: 99%
“…17 More relevant to the Philippines, a systematic review of EHDI programs in low-and middle-income countries in Asia revealed three of 82 studies describing "the use of ICT for storing and forwarding results, database management, and sending reminders for follow-up screening". 18 This HeLe evaluation centered on the NHS program and technical / technology inputs, based on the CDC guidelines for evaluating public health surveillance systems. We evaluated information quality (relevance, accuracy, completeness, timeliness) and system quality (availability, usability/ accessibility, functionality, comprehensive data capture, error reduction, and security).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of standardized protocols is evident in neonatal hearing screening practices ( 33 , 34 ). Despite this, there is a prevailing tendency toward recommending protocols involving the application of AABR due to its demonstrated higher specificity and reduced false positives in detecting hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…They stressed the need for an urgent implementation of universal neonatal hearing screening in all the healthcare facilities in the country at large. A review of early detection and intervention programs in low-and middle-income countries of Asia by Joshi et al (2022) [5] showed that a majority of the NBHS programs in India, primarily employed a two-step approach. Initially, either otoacoustic emission screening (utilizing Distortion Product or Transient Evoked emissions) or automated auditory brainstem response screening was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Audiologists were the professionals most commonly involved in conducting these screenings. Joshi et al (2022) [5] further reported that the screening tools and procedures employed in low-and middle-income countries were comparable to those in high-income countries but, there was a lack of standardized protocols within individual countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation